The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00421-009-1105-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of the VEGFR2 gene His472Gln polymorphism with endurance-related phenotypes

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) is essential to induce the full spectrum of VEGF angiogenic responses to aerobic training. In the present study, we examined the impact of the functional His472Gln polymorphism of the VEGFR2 gene on elite athlete status, endurance performance and muscle fibre type composition. Four hundred and seventy-one Russian athletes were prospectively stratified into four groups according to event duration, distance and type of activity, covering a spectrum from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…There was, however, no increase in protein expression for VEGFR1 in the same muscle during the same time period (Milkiewicz et al 2003). Recently, Ahmetov et al (2009) examined VEGFR2 allele frequencies in 471 elite Russian endurance athletes and 603 control subjects. The investigators reported that the VEGFR2 472Gln allele was prevalent in various types of endurance athletes, such as swimmers and road cyclists, relative to control subjects (Ahmetov et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was, however, no increase in protein expression for VEGFR1 in the same muscle during the same time period (Milkiewicz et al 2003). Recently, Ahmetov et al (2009) examined VEGFR2 allele frequencies in 471 elite Russian endurance athletes and 603 control subjects. The investigators reported that the VEGFR2 472Gln allele was prevalent in various types of endurance athletes, such as swimmers and road cyclists, relative to control subjects (Ahmetov et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ahmetov et al (2009) examined VEGFR2 allele frequencies in 471 elite Russian endurance athletes and 603 control subjects. The investigators reported that the VEGFR2 472Gln allele was prevalent in various types of endurance athletes, such as swimmers and road cyclists, relative to control subjects (Ahmetov et al 2009). The authors suggested that this phenotype in skeletal muscle may cause an increased affinity for VEGF binding.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, gene variations could be considered as molecular determinants maintaining the expression of the slow or fast myosin heavy chain isoforms of adult skeletal muscle. Indeed, several polymorphisms of genes involved in the calcineurin/NFAT pathway, mitochondrial biogenesis, glucose and lipid metabolism, cytoskeletal function, hypoxia/angiogenesis and circulatory homeostasis are reported to be candidate genetic markers for determination of muscle fibre composition (Zhang et al 2003, Ahmetov et al 2006, 2008, 2009 a , b ; Vincent et al 2007). One possible explanation for the relationship between α‐actinin‐3 deficiency ( ACTN3 XX genotype) and slow‐twitch muscle fibre phenotype observed previously, and confirmed in the present study, could be evidence that α‐actinins interact with signalling proteins, such as calcineurin (reviewed by Berman & North, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the His472-Gln polymorphism influences the efficiency of VEGF binding to VEGFR2 [169]. In a study of 182 endurance-oriented Russian athletes, the significantly higher frequency of the VEGFR2 472Gln allele compared to controls was reported [170]. Furthermore, the 472Gln allele was also shown to be significantly associated with a higher proportion of type I fibers of m. vastus lateralis (determined by immunohistochemistry) in both athletes (all-round speed skaters, n ¼ 23; age 20.4 AE 0.5 years) and physically active men (n ¼ 45; age 23.5 AE 0.4 years), and with a greater VO 2max in female rowers [170].…”
Section: Vegfr2 472gln Allelementioning
confidence: 95%